Psycholinguistic Means of Traumatic Memory Reorganization - Zasiekina, Larysa; Shevchuk, Olga (Psychological Prospects Journal, 2015)
The results of theoretical and empirical study of traumatic memory are highlighted in the article. The author propositional model of traumatic memory is proposed. The narrative method for propositional structure of respon-dendents’ narratings about traumatic event was used. The typology of traumatic events was revealed. The most frequent elements of propositions in the narratives with traumatic events were defined. Among them there are attitude (37,4 %), external object (23,5 %), external argument (15,1 %), internal argument (15,0 %), time (5,0 %), space (0,5 %) The main factors of traumatic memory reorganization and transforming it into episodic memory were analyzed. Two main directions of traumatic memory reorganization were studied. The first one is connected with making sense for traumatic event during narrating process and giving access to episodic memory and individual wellbeing. The second one is connected with small personal resource for making sense for traumatic event and highly emotional attitude to it which transform experienced traumatic event into post-traumatic stress disorder. The correlation between degree of traumatic memory reorganization and personality traits are revealed. Three types of typical propositional structures in the the narratives with traumatic events were analyzed, among them there are psycholinguistic, episodic and personal. The correlation of each propositional structure with individual attitude to traumatic event was described. It was revealed that while narrating the traumatic event individual focused on her/his attitude to it. Moreover, predominance of internal or external argument is connected with the individual complex of guilt and personal responsibility for traumatic event. Different propositional structures for respondents’ with high, middle and low levels of wellbeing were defined. The psycholinguistic peculiarities of narratives with traumatic events were revealed: low number of words, high sentence length, high indices of logical coherence and verbs.